Ingesting a high-dose carbohydrate solution during the cycle section of a simulated Olympic-distance triathlon improves subsequent run performance - McGawley, K.; Shannon, O.; Betts, J. (Applied Physiology, Nutrition, and Metabolism, 2012)
The well-established ergogenic benefit of ingesting carbohydrates during single-discipline endurance sports has only been tested once within an Olympic-distance (OD) triathlon. The aim of the present study was to compare the effect of ingesting a 2:1 maltodextrin/fructose solution with a placebo on simulated OD triathlon performance. Six male and 4 female amateur triathletes (age, 25 ± 7 years; body mass, 66.8 ± 9.2 kg; peak oxygen uptake, 4.2 ± 0.6 L·min-1) completed a 1500-m swim time-trial and an incremental cycle test to determine peak oxygen uptake before performing 2 simulated OD triathlons. The swim and cycle sections of the main trials were of fixed intensities, while the run section was completed as a time-trial. Two minutes prior to completing every quarter of the cycle participants consumed 202 ± 20 mL of either a solution containing 1.2 /min of maltodextrin plus 0.6 g·min-1 of fructose at 14.4% concentration (CHO) or a sugar-free, fruit-flavored drink (PLA). The time-trial was 4.0% ± 1.3% faster during the CHO versus PLA trial, with run times of 38:43 ± 1:10 min:s and 40:22 ± 1:18 min:s, respectively ( p = 0.010). Blood glucose concentrations were higher in the CHO versus PLA trial ( p < 0.001), while perceived stomach upset did not differ between trials ( p = 0.555). The current findings show that a 2:1 maltodextrin/fructose solution (1.8 g·min-1 at 14.4%) ingested throughout the cycle section of a simulated OD triathlon enhances subsequent 10-km run performance in triathletes.